Assessment of PM10 Exposure Risk in Communities Downwind and Upwind of Stone Milling Plants in Northeastern Thailand - Boonkhao, Laksanee; Pinpan, Savittri; Philabut, Aorawanya Philabut; Kantow, Supakan; Rattanachaikunsopon , Pongsak (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
PM10 particles can be inhaled and absorbed into the bloodstream and lymphatic systems.However, there is a lack of information in Thailand regarding the release of dust fromstone mill units and the potential health risks it poses to the surrounding community. Theaim of this research is to assess the health risks associated with PM10 exposure for residents of communities surrounding stone milling plants in Northeastern Thailand. Thestudy included a total of 225 households located both downwind and upwind of the stonemilling plants. Data were gathered by the conduct of a questionnaire to the participants,as well as the collection of PM10 particulate matter in the specified area. The collectionof PM10 was conducted following the established NIOSH method number 0600. Thenon-carcinogenic attributes of PM10 were analyzed based on the guidelines provided bythe Environmental Protection Agency. A descriptive statistical analysis was performed onthe collected data to determine various parameters such as frequency, percentage, average,maximum, and minimum values. The mean concentration of PM10 in the downwindcommunity was 0.024796 mg/m3 (S.D. = 0.0551), while in the upwind community itwas 0.000232 mg/m3 (S.D. = 0.0002). The community exhibited Hazard Quotient (HQ)values that were considered acceptable, along with lower exposure levels. However, theresidents in the surrounding areas of the stone mill may be exposed to dust from a varietyof sources, including transportation, construction, and the burning of agricultural material. The current study’s findings are anticipated to provide important information to improve the understanding of PM10exposure in populations living near stone milling plants.